STRUCTURAL AND ECONOMIC VIABILITY OF 2D/3D FINITE ELEMENT ANALYSIS OF CONICAL ARCHED ROOF TRUSS (Nigerian Journal of Technology, 2014)
Arch and conical roof trusses are employed when dealing with large span roof trusses. But a combination of the two geometrical shapes may lead to a better economical sections and a means of dealing with larger spans of roof truss that are not suitable for an arch or conical roof truss. Consequently, this paper examines the structural and economic viability of arched conical roof truss system based on 2D/3D finite element method analysis. Analysis of the results showed that truss members were subjected to higher axial forces in 2D analysis than 3D analysis, which will result to overdesign of the structural members and the attendant high construction cost. There are some variations observed in the axial forces for trusses located at edges of polygon when compared with the trusses located mid-point between two polygonal edges. This observation is quite significant in the sizes of the steel section properties of the members as well as in the fabrication and installation cost.